Pemberdayaan Kelompok Nelayan dalam Membudidayakan Kerang Dara sebagai Pendapatan Ekonomi Rakyat di Kampung Nelayan Belawan 1 Medan - Yuni, Eri; Yunilas, Yunilas; Trisna, Ade; Lubis, Abdul Haris (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is a field survey and a group of Belawan fishermen with the aim of providing training on how fishermen can cultivate kerrang from the area where they live. This service also involves 5 groups of kerrang dara cultivators, where their economic life depends on the livelihood of kerrang dara, and dedication This changes them from searching for kerrang in the sea to now being able to cultivate them in their own yard, so that there is no struggle for land where the kerrang live.